Ethnic disparities in patients with head and neck cancer undergoing palliative care and its impact on clinical outcomes: a systematic review - Moura, Anne Evelyn Oliveira; Epstein, Joel B.; Santos-Silva , Alan Roger; Santos, Erison Santana dos (Journal of Oral Diagnosis, 2025)
Objective: This study aimed to investigate ethnic disparities in patients with head and neck cancer undergoing palliative care and their impact on clinical outcomes. Methods: This review was conducted according to the Pre-ferred Reporting Items for Systematic Reviews and Meta-Analyses. Five electronic databases (Medline/PubMed, SCOPUS, EMBASE, Web of Science, and LILACS), in addition to the gray literature, were used. Results: Eleven studies (497,671 patients) were included in the qualitative analysis, all of which were based in the United States of America. A small portion of the total sample was in PC (5.7%). Most patients in PC were white/Caucasian (76.0%), however, 78.7% of the total sample of this systematic review were white patients. Conclusion: Based on the data available in the literature, it was not possible to conclude whether there is ethnic disparity in access to palliative care for patients with head and neck cancer, and whether there ethnicity influences clinical outcomes.